OECD Agricultural Trade Reforms Impact on India's Prices and Producers Welfare - Surabhi Mittal (Indian Council for Research on International Economic Relations (ICRIER), 2007)
Rich countries use a combination of domestic market interventions and border protection or export subsidies as a part of their domestic policies. Developed countries such as the United States and the European Union (EU) resort to trade distorting policies to make their crop more competitive - both groups maintain high domestic prices for producers, stimulate production, and thus distort prices in the world market. The distorting effects of international trade can be distinguished between consumer surplus, producer surplus and tariff revenue approaches. The present paper emphasizes on the welfare of the producers with the main focus on small farmers. The analysis presented in the paper is an approximation of the general general equilibrium analysis. The four parts of this approximation are: first, the estimation of the world price effect of removal of OECD (Organisation for Economic Co-operation and Development) distortions; second, estimation of the effects of changes in world prices on domestic prices through a price transmission model; third, estimation of the impact on domestic production through a supply response model; and, four, the estimation of changes in supply and welfare on the poor small farmers. The simulation exercise shows that due to elimination of subsidies in OECD countries the world crop prices are expected to rise. The results confirm that the depressed world prices can be corrected by removal of OECD subsidies, but the challenge for India remains: How much can these price corrections benefit the farmers? India's domestic price response to this world price change is very small for rice and wheat and slightly better for cotton and sugar. On the production front, with reduction in subsidies and rising of the world price, the production in OECD countries would decline, but it is not very clear if this would have a discernable effect on India's production. In response to the rise in world price, this paper concludes that this change would have almost negligible impact on India's production for rice and wheat and a marginal increase in the production of cotton and sugar. The welfare impact on small farmers based on these changes is also estimated. The important fact to be observed in this study is that the developed countries' policies protecting their farming sector critically affect the lives of billions of people who depend on agriculture in developing countries.
Keywords: F13; F17; Q17; 330; OECD Agriculture; Trade Policy; Subsidy Elimination; Producer Welfare; Exportsubvention; Außenwirtschaftspolitik; OECD-Staaten-seitig; Handelsliberalisierung; Wirkungsanalyse; Exportpreis; Entwicklungsländer; Schätzung